Islam Nusantara: Islam & Nasionalisme - Efi Afifi (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M) STAI Miftahul Huda Subang, 2022)
Indonesian society has experienced a positive historical flow in building their national spirit. The national awakening that occurred in the 20th century was marked by resistance and struggle against colonialism and colonialism to liberate Indonesia. And in the historical record, Muslims with their nationalist spirit have a very large role and contribution in liberating and forming the Unitary State of the Republic of Indonesia (NKRI). The spirit of nationalism of religious leaders (ulama) in the pre-independence period was also the substance of the idea of ​​Nusantara Islam. In the idea of ​​Islam Nusantara, there are at least two major and major issues; First, is the issue of the relationship between Islam and local culture, which provoked the emergence of the term indigenization of Islam and this is the main and most central issue of this much-talked-about Nusantara Islam discourse. So there are not a few assumptions, that Islam Nusantara is part of an effort to localize universal Islam and even demean Islam itself. This assumption is certainly not correct, when referring to the main substance of Nusantara Islam, which has actually been carried out by the guardians in spreading Islam in the archipelago. Second, is the issue of Islam and Nationalism or Islam and the State. The second issue is no less provoking debate both in the academic and non-academic worlds.